PENYIMPANGAN PRINSIP KERJA SAMA SEBAGAI PEMBENTUK HUMOR WEB SERIES IMPERFECT SEASON 2 EPISODE 1-5 - Dinda Ayuni Setiawan , Andik Yuliyanto (TRANSFORMATIKA, 2023)
The "Imperfect Season 2 Episodes 1-5" web series shows intentional deviations from Grice's cooperative principles to create humorous effects. This study aims to describe the deviations from cooperative principles in the web series "Imperfect Season 2 Episodes 1-5". The research used a qualitative descriptive method, using data from actors' dialogues that deviate from cooperative principles. Data collection was done through observation and note-taking techniques. Data analysis involves selecting and classifying the deviations based on the four maxims. The research results indicate deviations in all four maxims: quantity, quality, relevance, and manner. Deviations in the maxim of quantity are shown through understatements and overstatements. Deviations in the maxim of quality are demonstrated by statements that contradict facts and are fabricated. The maxim of relevance is shown by utterances unrelated to the topic of the dialogue. The maxim of manner is shown by unclear and not coherent dialogues, ambiguous and convoluted.